Substance Use Disorder and COVID-19; Forensic Medicine and Pharmacology Perspectives: A Concise Narrative Review - Ahmed Ali; Torki Al-Zughaibi; Assmaa A. Shaker (Arab Journal of Forensic Sciences & Forensic Medicine, 2021)
Many investigations have confirmed the link between a substance use disorder (SUD) and the COVID-19 pandemic's increased risk of infection and consequences. This narrative review aims to understand these issues from a pharmacological standpoint, as well as the pandemic's impact on forensic medicine. Research and review articles included in this review were selected through an extensive search of databases such as PubMed and the use of appropriate keywords e.g. “substance use disorder” and “COVID-19”. Due to a weakened immune system and degeneration of the respiratory system's defense systems, SUDs have been shown to increase the risk of COVID-19 infection. Furthermore, some substances raise pro-inflammatory mediators, exposing the body to a cytokine storm. SUD frequently causes secondary comorbidities, such as the liver, lung and cardiovascular disease, complicating the treatment of COVID-19 infections. Some misused substances can compromise the treatment's effectiveness or safety. This study also looked at the effects of the pandemic on forensic medicine. It underlines the importance of developing safe forensic examination procedures and methodologies during pandemics. The use of narcotic substances was documented as one of the reasons for the increase in the frequency of COVID-19 and the severity of its repercussions.